Collecting and preserving insects and arachnids : (ARC, 2000)
This book includes many part: important of taxonomy and reference collections in applied research, introduction to zoological nomenclature, the higher classification of insects and arachnids, collecting methods, killing and temprorary storage, preservation, labelling, accessioning and dispatching, permanent storage and curation, collectors code of practice.